Cutaneous metastasis from carcinoma of lung - Smita Pathak; Sneha R Joshi; Janice Jaison; Dipak Kendre (Wolters Kluwer Medknow Publications, 2013)
A 65-year-old male with a history of smoking since 30 years presented with breathlessness, hemoptysis, multiple swellings all over the body, and weakness in September 2010 at our hospital. Clinically, a diagnosis of chronic obstructive pulmonary disease (COPD) with cutaneous lymphoma or soft tissue tumor was made. Chest X-ray (CXR) and computed tomography (CT) scan revealed a neoplastic lesion in the right lung with secondary cavitation. Biopsy of the cutaneous nodules showed metastatic deposits from squamous cell carcinoma. Metastatic skin cancer is a relatively rare complication of internal malignancy. The clinical features of metastatic skin disease vary enormously. They may present as erysipeloid, sclerodermoid, alopecia neoplastica or in an inflammatory or bullous form or as multiple nodules as in our case. A high index of suspicion for metastatic deposits is required in an elderly male patient who is a known case of lung cancer or even one who is a chronic smoker and presents with such cutaneous lesions.